Childhood under threat - Bellamy, Carol (New York The United Nations Children's Fund, 2004)
The gap between the reality and the ideal of childhood is the focus of the report : what childhood means for countries, and what must be done if the rights of all children are to protected , if the millennium development goals are to be met, and if we are to successfully build a world fit for children and for all of us
Includes index
osc 31/01/2019
Loans
Keywords: Child welfare; War and society; Children; HIV/ AIDS - social aspects; Developing countries